NTRK and other recently described kinase fusion positive uterine sarcomas: A review of a group of rare neoplasms. Issue 3 (11th November 2020) - Croce, Sabrina; Hostein, Isabelle; McCluggage, W Glenn
Abstract: The landscape of uterine sarcomas has greatly expanded in recent years to include neoplasms with recurrent gene fusions, such as BCOR and YWHAE translocated high‐grade endometrial stromal sarcomas. Sophisticated molecular techniques have also resulted in the description of "new" entities associated with recurrent kinase fusions involving NTRK and RET as well as COL1A1‐PDGFB rearranged uterine sarcomas. These rare neoplasms will be discussed in this review, highlighting that some of the underlying molecular events are clinically actionable and potentially susceptible to targeted therapy. While relatively few of these neoplasms have been described to date, likely being previously lumped under the spectrum of undifferentiated uterine sarcoma, the number of cases will expand in the future given their recognition and the increasing availability of molecular testing. These neoplasms have overlapping morphology (often with a "fibrosarcoma‐like" appearance) and immunohistochemical features, and are characterized by variable clinical outcomes. Although immunohistochemistry may assist in some cases, a definitive subclassification requires confirmatory molecular studies. As these molecular assays may not be routinely available in most laboratories, referral to reference centers may be needed. In order to assist the pathologist, we suggest a diagnostic algorithm for routine practice when dealing with a malignant or potentially malignant uterine spindle cell neoplasm.